Research progress on Sertoli cell secretion during spermatogenesis - Xiao, Yao; Zhang, Jingyi; Guan, Yanxin; Wang, Meijing; Liu, Dehong; Xiong, Shengxi; Li, Junjun; Yu, Xujun (Frontiers in Endocrinology, 2025)
Sertoli cells (SCs), as the somatic cells in the testis of male mammals, play a crucial role in the close association with germ cells. The blood-testicular barrier (BTB), established by their tight junctions, provides immune protection to germ cells, leading to their characterization as "sentinel" cells. Moreover, the physiological process of testicular development and spermatogenesis in male animals is intricately tied to the secretory activities of SCs. These cells secrete a diverse array of proteins and cytokines that interact with various targets, working in concert with mechanisms in the spermatogenesis pathway and contributing to each stage, from spermatogonial cell division to the maturation of spermatozoa. Hence, the secretory products of SCs are pivotal in fostering germ cell development and directing the appropriate maturation of sperm. This study is dedicated to investigating the varied secretions of SCs, outlining their critical functions throughout distinct phases of spermatogenesis, thus elucidating the substantial influence of SC secretion on male fertility. Furthermore, it offers valuable perspectives on reproductive disorders stemming from irregular spermatogenesis in clinical contexts.